PENGARUH KARAKTERISTIK INDIVIDU, DISIPLIN KERJA DAN IKLIM ORGANISASI TERHADAP KINERJA PEGAWAI BADAN PENGELOLA KEUANGAN DAN ASET DAERAH KABUPATEN BATU BARA - Yessi Amelia Agustina Siregar; Ilham Wijaya; Adli Sofyan; Rudi Arianto; Ali Adam (JEKKP (Jurnal Ekonomi, Keuangan dan Kebijakan Publik), 2021)
This research discusses about the influences of   individual characteristics, work discipline  and  organizational  climate  on  employees’  performance  at  Regional Fund and Asset Management Office of Batu  Bara Regency. The aim of this research is to analyse influences of  individual characteristics, work discipline and organizational climate both partially and simultaneously on employees’ performance at the office. This is a quantitative research with total sampling technique. The sample is 64 employees. Results show that each independent variable;   individual characteristics, work discipline and organizational climate, partially influences employees’ performance positively and significantly. individual characteristics has tcount  value 7,088 and level of significance 0.000, work discipline has 3,530 and 0.001, and organizational climate has 3,802 and 0.000. Simultaneously, individual characteristics, work discipline and organizational  climate have significant  and  positive influences  on  employees’ performance at Regional Fund and Asset Management Office of Batu Bara Regency with Fcount value 58,118 and level of significance 0.000.